2015
DOI: 10.5511/plantbiotechnology.15.1023b
|View full text |Cite
|
Sign up to set email alerts
|

Identification of furostanol glycoside 26-<i>O</i>-β-glucosidase involved in steroidal saponin biosynthesis from <i>Dioscorea esculenta</i>

Abstract: Steroidal saponins are natural surfactants with various biological activities, and the tubers of Dioscorea, known as yam, contain a furostanol glycoside protodioscin and a spirostanol glycoside dioscin, which are valuable saponins required for semi-synthetic production of pharmaceutical steroidal drugs. Steroidal saponins are biosynthesized from cholesterol via several steps of oxygenation and transglycosylation, and a β-glucosidase is involved in the hydrolytic conversion from furostanol glycosides to spirost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 27 publications
0
9
0
2
Order By: Relevance
“…In addition to CYP enzymes, a specific C-26 glucosyltransferase and a 26- O -β-glucosidase are proposed to catalyze the reactions which facilitate the closure of diosgenin ring E and ring F (Scheme 1) [20,26,32]. Within the UGT unigenes with a length above 1000 bps in the T. foenum-graecum transcriptome, there were 21 UGT unigenes that were significantly induced by the MeJA elicitation (Table S3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to CYP enzymes, a specific C-26 glucosyltransferase and a 26- O -β-glucosidase are proposed to catalyze the reactions which facilitate the closure of diosgenin ring E and ring F (Scheme 1) [20,26,32]. Within the UGT unigenes with a length above 1000 bps in the T. foenum-graecum transcriptome, there were 21 UGT unigenes that were significantly induced by the MeJA elicitation (Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, there were 11 glucosidase annotated unigenes with a length above 1000 bps that were induced by the MeJA elicitation (Table S4). A phylogenetic analysis showed that the candidates of cluster-2140.60643 and cluster-2140.23403 showed a relatively closer relationship with the isoflavone β-glucosidase from Glycine max [33] and the furostanol glycoside 26- O -β-glucosidases from Dioscorea esculenta [20] and Costus speciosus [19] (Figure S5), suggesting that they may be the C-26-β-glucosidase candidates during diosgenin biosynthesis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The biochemical characterization of DeF26G revealed that it was a furostanol glycoside 26-O-β-glucosidase that was involved in the conversion of protodioscin (furostanol saponin) to dioscin (spirostanol saponin). The expression of the DeF26G1 gene in the leaves of Dioscorea esculenta was higher than that in the tubers (Nakayasu et al 2015). Using Illumina deep sequencing Dioscorea composita was used to analyze the transcriptome of 18-month-old Dioscorea composita.…”
Section: Dioscorea Speciesmentioning
confidence: 99%
“…Recently, we have seen little progress on advanced molecular studies of Dioscorea. Nakayasu et al [195] have performed comparative transcriptome analysis of high saponin containing yams i.e. D. esculenta and D. cayenensis, and a low saponin containing, D. alata, for understanding biosynthesis of steroidal saponins and identified the β-glucosidase (DeF26G1) gene to be responsible for higher accumulation of saponins in D. esculenta.…”
Section: Nutritional Composition Of Dioscorea (Yam) a Neglected Staple Tuber Crop Of The Tribal Communitiesmentioning
confidence: 99%